2019
DOI: 10.1111/jopy.12470
|View full text |Cite
|
Sign up to set email alerts
|

Passion and moral disengagement: Different pathways to political activism

Abstract: Objective: Four studies examined the relationship between motivational imbalance-the degree to which a goal dominates other goals-and political activism. Method: Based on the dualistic model of passion (Vallerand, 2015) and recent theorizing on violent extremism (Kruglanski, Jasko, Chernikova, Dugas, & Webber, 2017), we predicted that obsessive passion (OP), which facilitates alternative goal suppression, would increase support for violent political behaviors. In contrast, we predicted that harmonious passion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 61 publications
4
36
0
1
Order By: Relevance
“…This may be due to the online setting of our survey, although research established that online and laboratory investigations usually give effect sizes of the same magnitude (see Paolacci et al, 2010). Besides, our effects were of size that is typical in research on Significance Quest Theory research (e.g., Webber et al, 2018; Bélanger, Schumpe et al, 2019). Therefore, we think these might reflect accurate parameter estimates (especially given the large sample under investigation).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This may be due to the online setting of our survey, although research established that online and laboratory investigations usually give effect sizes of the same magnitude (see Paolacci et al, 2010). Besides, our effects were of size that is typical in research on Significance Quest Theory research (e.g., Webber et al, 2018; Bélanger, Schumpe et al, 2019). Therefore, we think these might reflect accurate parameter estimates (especially given the large sample under investigation).…”
Section: Discussionmentioning
confidence: 82%
“…According to Significance Quest Theory, individuals have a fundamental need to feel meaningful: they need to perceive that their actions have purpose (e.g., deriving satisfaction from one’s work), to feel that they are respected and achieve socially valued life-goals (e.g., having a desirable social status, being acknowledged for contributing to one’s community; see Bélanger, Schumpe et al, 2019). When this need is threatened, individuals will be more motivated to engage in actions aimed at restoring their sense of significance, which can lead them to join groups that offer strong social support, clear-cut narratives to make sense of their situation and social rewards for radical action (i.e., extremist religious or political groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the purview of political activism, Rip et al (2012) found that Quebec nationalists who scored higher on HP preferred peaceful and democratic ways of furthering their ideology, whereas those scoring higher on OP showed a proclivity toward aggressive and radical methods. Extending these findings, experimental evidence suggests that the relationship between OP (vs. HP) and radical (vs. peaceful) activism is mediated by moral disengagement, that is, people’s ability to deactivate moral self-regulatory processes, allowing unethical behavior—a proclivity related exclusively to OP (Bélanger, Schumpe, Nociti, et al, 2019). Although these results shed light on the cognitive mechanisms linking OP to political violence, they do not address the social components associated with radicalization.…”
Section: The Dualistic Model Of Passionmentioning
confidence: 92%
“…To examine these questions, we build on prior work linking passion for a cause to violent political activism (Bélanger, Schumpe, Nociti, et al, 2019). Consistent with the 3N model of radicalization (Bélanger, Moyano, et al, 2019; Kruglanski Bélanger, & Gunaratna, 2019; Webber & Kruglanski, 2017) and uncertainty-identity theory (Hogg, 2000, 2007, 2009), we propose a trajectory whereby individuals struggling to fulfill their need for personal significance (i.e., obsessively passionate individuals), seek solace in radical networks that provide self-certainty, which predisposes them to embrace ideological narratives that condone political violence.…”
mentioning
confidence: 99%